Preparation method of O3 / O2 heterogeneous composite lithium cobalt oxide positive electrode material
Patent Information
- Application Number
- CN202611495040.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
该工艺存在以下致命缺陷:其一,必须引入钠盐杂质,且钠离子残留难以彻底清除,会严重破坏4.7V高电压界面稳定性,加剧容量衰减;其二,离子交换工序繁琐、能耗较高、生产周期长,导致量产成本偏高且产品一致性欠佳;其三,离子置换过程易产生大量晶体缺陷,晶格完整性较差,无法满足4.7V超高压长期循环需求,高压循环稳定性的提升效果有限
1、本发明摒弃行业唯一主流的锂钠离子交换制O2相技术,首创无钠原位高温烧结工艺,一步直接构建O3/O2异相结构,消除钠离子残留缺陷;制备的正极材料用于锂离子电池时,可避免杂质对4.7V超高电压界面的破坏;同时简化了工艺流程、缩短了生产周期、降低了能耗与物料成本,适配现有钴酸锂量产生产线。
Smart Images

Figure CN123017950A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery cathode material technology, specifically relating to a method for preparing an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material. Background Technology
[0002] Lithium cobalt oxide (LiCoO2), with its ultra-high compaction density, excellent rate performance, and mature mass production process, has become a core cathode material for high-end consumer electronics and ultra-thin digital products. To overcome the bottleneck of battery energy density, the industry is currently continuously increasing the operating voltage of lithium cobalt oxide from 4.5V to an ultra-high voltage level of 4.7V. This significantly improves battery capacity and is the core development direction for the next generation of high-energy-density lithium batteries.
[0003] However, the ultra-high voltage of 4.7V places higher demands on the structural stability of lithium cobalt oxide. Under ultra-high voltage conditions, lithium ions undergo deep intercalation and deintercalation, leading to drastic anisotropic expansion and contraction of the crystal lattice and a rapid accumulation of interlayer stress. This can easily trigger irreversible phase transitions from the O3-type layered structure to the spinel phase, rock salt phase, and even the O1 phase, resulting in particle cracking and structural collapse. Simultaneously, under the high-voltage, strong oxidizing environment, electrolyte decomposition intensifies, interfacial side reactions increase significantly, and the cobalt ion dissolution rate increases exponentially. These factors ultimately lead to rapid capacity decay and a significantly shortened cycle life, severely restricting the large-scale application of 4.7V high-voltage lithium cobalt oxide.
[0004] To address the stability issue at 4.7V high voltage, existing technologies have developed O3 / O2 heterogeneous composite lithium cobalt oxide systems. These systems utilize the coherent interface of the two phases to buffer lattice stress, thus improving high-voltage structural stability to some extent. However, currently published and pending patents and technologies related to O3 / O2 composite lithium cobalt oxide all rely on a lithium-sodium ion exchange process: a sodium-based cobaltate precursor must first be prepared, followed by a lithium-sodium substitution reaction to generate the O2 phase, and then sintering to obtain the O3 / O2 composite structure. This process has the following fatal flaws: First, it inevitably introduces sodium salt impurities, and the residual sodium ions are difficult to completely remove, severely compromising the stability of the 4.7V high-voltage interface and exacerbating capacity decay. Second, the ion exchange process is cumbersome, energy-intensive, and has a long production cycle, resulting in high mass production costs and poor product consistency. Third, the ion exchange process easily generates numerous crystal defects, leading to poor lattice integrity, which cannot meet the long-term cycling requirements of 4.7V ultra-high voltage, and the improvement in high-voltage cycling stability is limited.
[0005] In addition, existing high-voltage modification technologies mostly employ doping or coating strategies, which make it difficult to simultaneously solve multiple key problems such as bulk phase structure collapse, cobalt dissolution, and interfacial side reactions under ultra-high voltage of 4.7V.
[0006] Therefore, developing a highly stable O3 / O2 heterogeneous composite lithium cobalt oxide that requires no lithium-sodium ion exchange, leaves no sodium salt residue, can be prepared by in-situ sintering, and is compatible with an ultra-high voltage of 4.7V is a technical bottleneck that urgently needs to be overcome in this field. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for preparing O3 / O2 heterogeneous composite lithium cobalt oxide cathode material.
[0008] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows: A method for preparing an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material includes the following steps: S1: Weigh out the cobalt source, lithium source and dopant element M in nitrate or acetate according to the molar ratio Li:(Co+M)=1.02~1.05:1 and Co:M=50~250:1, then add deionized water to prepare a slurry, and spray dry the slurry to obtain the precursor powder. S2: The precursor powder is placed in a tube furnace and heated to 850-950°C at a heating rate of 2-5°C / min under an oxygen atmosphere. It is then sintered at a constant temperature for 8-12 hours and cooled with the furnace to obtain a heterogeneous intermediate with an O3 / O2 heterogeneous structure. S3: Mix the heterogeneous intermediate, the nano-oxide of doped element X, and lithium carbonate, with 100 parts by mass of heterogeneous intermediate, 1-3 parts by mass of nano-oxide, and 0.5-1.5 parts by mass of lithium carbonate; add ethanol as a dispersion medium and ball mill for 3-5 hours, and dry to obtain doped mixed powder. S4: Place the doped mixed powder in a tube furnace, heat it to 500-650°C at a heating rate of 1-3°C / min under an oxygen atmosphere, hold it at that temperature for 4-6 hours, and then cool it with the furnace; pulverize the calcined product and pass it through a 300-mesh sieve to obtain an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material with doped element X on the surface.
[0009] Furthermore, in step S1, the cobalt source is at least one of cobalt tetroxide and cobalt carbonate.
[0010] Furthermore, in step S1, the lithium source is at least one of lithium carbonate and lithium hydroxide.
[0011] Furthermore, in step S1, the doping element M is at least one of Al, Mg, Zr, and Ti.
[0012] Furthermore, in step S3, the doping element X is at least one of La, Ce, Y, and Sr.
[0013] Furthermore, in step S2, the oxygen flow rate is 5~10L / min.
[0014] Furthermore, in step S4, the oxygen flow rate is 2~8 L / min.
[0015] An O3 / O2 heterogeneous composite lithium cobalt oxide cathode material is obtained by the preparation method described above. The cathode material includes a core crystal structure and a doped protective shell coating the core crystal structure. The core crystal structure has LiCo... 1-x M x The composition of O2, wherein the doped protective shell has LiCo 1-y X y The composition of O2, wherein 0.01≤x≤0.05, 0.02≤y≤0.08; the chemical composition of the cathode material is represented as LiCo. 1-x M x O2@LiCo 1-y X y O2.
[0016] A positive electrode sheet includes a positive active material layer, wherein the positive active material layer comprises the O3 / O2 heterogeneous composite lithium cobalt oxide positive electrode material as described above.
[0017] A lithium-ion battery includes a positive electrode, wherein the positive electrode is as described above.
[0018] The beneficial effects that this invention can achieve are as follows: 1. This invention abandons the industry's only mainstream technology of lithium sodium ion exchange to produce O2 phase, and pioneers a sodium-free in-situ high-temperature sintering process to directly construct an O3 / O2 heterogeneous structure in one step, eliminating sodium ion residual defects. When the prepared cathode material is used in lithium-ion batteries, it can avoid the damage of impurities to the 4.7V ultra-high voltage interface. At the same time, it simplifies the process flow, shortens the production cycle, reduces energy consumption and material costs, and is compatible with existing lithium cobalt oxide mass production lines.
[0019] 2. The O3 / O2 coherent interface formed by in-situ sintering of the present invention has a tight bond and very few crystal defects. Compared with the composite phase structure prepared by ion exchange method, the lattice integrity is higher. It can effectively buffer the huge lattice stress generated by deep delithiation at 4.7V, completely suppress the irreversible phase transformation of the layered phase to harmful phases such as spinel, rock salt, and O1 phase, and prevent particle cracking and structural collapse.
[0020] 3. Doping element M enhances the stability of the Co-O bond and suppresses cobalt dissolution under 4.7V high voltage; the surface doped protective shell blocks electrolyte side reactions and reduces interfacial impedance. The cathode material prepared by this invention has a compaction density ≥4.2g / cm³, and the battery's capacity retention rate after 50 cycles at 4.7V ultra-high voltage 1C is ≥79%.
[0021] 4. The cathode material prepared by this invention has a high density. When used in lithium-ion batteries, the lithium-ion batteries have comprehensive performance of high capacity and low degradation, which is suitable for ultra-high energy density consumer electronics products such as flagship smartphones, ultra-thin laptops, and high-end TWS devices. At the same time, it meets the 4.7V high voltage application requirements of small drones and high-end energy storage power batteries. Attached Figure Description
[0022] Figure 1 The XRD patterns of the cathode materials obtained in Example 1 and Comparative Example 1 of this invention are shown.
[0023] Figure 2 yes Figure 1 Magnified view of the (003) crystal plane.
[0024] Figure 3 yes Figure 1 Magnified view of the (104) crystal plane.
[0025] Figure 4 This is a SEM image of the cathode material obtained in Example 1 of the present invention.
[0026] Figure 5 This is a SEM image of the cathode material obtained in Comparative Example 1.
[0027] Figure 6 The image shows the cycle performance curves of batteries prepared using the cathode materials obtained in Example 1 and Comparative Example 1 at 4.7V and 1C. Detailed Implementation
[0028] Unless otherwise specified, the reagents, equipment and materials described in the following examples and comparative examples are commercially available. Example 1
[0029] This embodiment discloses a method for preparing an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material, including the following steps: S1: Weigh 100g of cobalt tetroxide, 47.32g of lithium carbonate, and 2.1g of aluminum nitrate to make Li:(Co+Al)=1.02:1 and Co:Al=126:1; add 200mL of deionized water to prepare a slurry with a solid content of 42.8wt%, and spray dry (inlet temperature 210℃, outlet temperature 90℃) to obtain precursor powder.
[0030] S2: The precursor powder was placed in a tube furnace and heated to 900℃ at a rate of 3℃ / min under an oxygen atmosphere (oxygen flow rate 8L / min). It was then sintered at this temperature for 10 hours and cooled in the furnace to obtain a heterogeneous intermediate. XRD refinement results: O3 phase 85 mol%, O2 phase 15 mol%.
[0031] S3: Take 100g of intermediate, 2g of nano lanthanum oxide, and 1g of lithium carbonate, add ethanol, ball mill at 400r / min for 4h, and dry to obtain doped mixed powder.
[0032] S4: Place the doped powder in a tube furnace and heat it to 580℃ at a rate of 2℃ / min under an oxygen atmosphere (oxygen flow rate 5L / min), hold for 5 hours, and then cool with the furnace; pulverize and pass through a 250-mesh sieve to obtain the target material LiCo. 0.98 Al 0.02 O2@LiCo 0.95 La 0.05 O2.
[0033] Product characteristics: Shell thickness 1 nm (TEM); O3:O2 = 17:3 ≈ 5.67:1; The compacted density is 4.28 g / cm³.
[0034] Battery performance: 4.7V / 1C cycle retention rate after 50 cycles: 90%.
[0035] Example 2 This embodiment discloses a method for preparing an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material, including the following steps: S1: Weigh 100g cobalt carbonate, 21.13g lithium hydroxide, 1.8g magnesium nitrate, and 1.2g zirconium nitrate to make Li:(Co+Mg+Zr)=1.03:1 and Co:(Mg+Zr)=53:1; add 200mL of deionized water to prepare a slurry with a solid content of 35.9wt%, and spray dry (inlet temperature 200℃, outlet temperature 85℃) to obtain precursor powder.
[0036] S2: The precursor powder was placed in a tube furnace and heated to 880℃ at a rate of 2℃ / min under an oxygen atmosphere (oxygen flow rate 6L / min). It was then sintered at this temperature for 12 hours and cooled in the furnace to obtain a heterogeneous intermediate. XRD refinement results: O3 phase 90 mol%, O2 phase 10 mol%.
[0037] S3: Take 100g of intermediate, 1.5g of nano-cerium oxide, and 0.8g of lithium carbonate, add ethanol, ball mill at 350r / min for 5h, and dry to obtain doped mixed powder.
[0038] S4: The doped powder was placed in a tube furnace and heated to 550°C at a rate of 1.5°C / min under an oxygen atmosphere (oxygen flow rate 3L / min), held at that temperature for 6 hours, and then cooled with the furnace. The powder was then pulverized and passed through a 300-mesh sieve to obtain the target material LiCo. 0.975 Al 0.025 O2@LiCo0.962 La 0.038 O2.
[0039] Product characteristics: Shell thickness 0.5 nm (TEM); O3:O2 = 9:1; The compacted density is 4.22 g / cm³.
[0040] Battery performance: The retention rate after 50 cycles at 4.7V / 1C is 79%.
[0041] Example 3 This embodiment discloses a method for preparing an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material, including the following steps: S1: Weigh 100g of cobalt tetroxide, 48.48g of lithium carbonate, and 2.5g of titanium nitrate to make Li:(Co+Ti)=1.05:1 and Co:Ti=147:1; add 200mL of deionized water to prepare a slurry with a solid content of 42wt%, and spray dry (inlet temperature 210℃, outlet temperature 90℃) to obtain precursor powder.
[0042] S2: The precursor powder was placed in a tube furnace and heated to 920℃ at a rate of 4℃ / min under an oxygen atmosphere (oxygen flow rate 9L / min). It was then sintered at this temperature for 9 hours and cooled in the furnace to obtain a heterogeneous intermediate. XRD refinement results: O3 phase 95 mol%, O2 phase 5 mol%.
[0043] S3: Take 100g of intermediate, 2.2g of nano-yttrium oxide, and 1.2g of lithium carbonate, add ethanol, ball mill at 450r / min for 3.5h, and dry to obtain doped mixed powder.
[0044] S4: The doped powder was placed in a tube furnace and heated to 600°C at a rate of 3°C / min under an oxygen atmosphere (oxygen flow rate 5L / min), held at that temperature for 4.5 hours, and then cooled with the furnace. The powder was then pulverized and passed through a 250-mesh sieve to obtain the target material LiCo. 0.978 Al 0.022 O2@LiCo 0.945 La 0.055 O2.
[0045] Product characteristics: Shell thickness 1.5 nm (TEM); O3:O2 = 19:1; The compacted density is 4.25 g / cm³.
[0046] Battery performance: The retention rate after 50 cycles at 4.7V / 1C is 86%.
[0047] Example 4 This embodiment discloses a method for preparing an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material, including the following steps: S1: Weigh 100g cobalt carbonate, 21.20g lithium hydroxide, 1.5g aluminum nitrate, and 1.0g titanium nitrate to make Li:(Co+Al+Ti)=1.0.4:1 and Co:(Al+Ti)=81:1; add 200mL of deionized water to prepare a slurry with a solid content of 42wt%, and spray dry (inlet temperature 210℃, outlet temperature 90℃) to obtain precursor powder.
[0048] S2: The precursor powder was placed in a tube furnace and heated to 900℃ at a rate of 3℃ / min under an oxygen atmosphere (oxygen flow rate 7L / min). It was then sintered at this temperature for 11 hours and cooled in the furnace to obtain a heterogeneous intermediate. XRD refinement results: O3 phase 97 mol%, O2 phase 3 mol%.
[0049] S3: Take 100g of intermediate, 1.8g of nano-strontium oxide, and 1g of lithium carbonate, add ethanol, ball mill at 400r / min for 4h, and dry to obtain doped mixed powder.
[0050] S4: Place the doped powder in a tube furnace and heat it to 590℃ at a rate of 2℃ / min under an oxygen atmosphere (oxygen flow rate 2L / min), hold for 5 hours, and then cool with the furnace; pulverize and pass through a 250-mesh sieve to obtain the target material LiCo. 0.977 Al 0.023 O2@LiCo 0.958 La 0.042 O2.
[0051] Product characteristics: Shell thickness 1.5 nm (TEM); O3:O2 = 97:3 ≈ 32.3:1; The compacted density is 4.24 g / cm³.
[0052] Battery performance: The retention rate after 50 cycles at 4.7V / 1C is 84%.
[0053] Example 5 This embodiment discloses a method for preparing an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material, including the following steps: S1: Weigh 100g of cobalt tetroxide, 47.89g of lithium carbonate, and 2.0g of magnesium nitrate to make Li:(Co+Mg)=1.03:1 and Co:Mg=92:1; add 200mL of deionized water to prepare a slurry with a solid content of 42wt%, and spray dry (inlet temperature 210℃, outlet temperature 90℃) to obtain precursor powder.
[0054] S2: The precursor powder was placed in a tube furnace and heated to 890℃ at a rate of 2.5℃ / min under an oxygen atmosphere (oxygen flow rate 6L / min). It was then sintered at this temperature for 10 hours and cooled in the furnace to obtain a heterogeneous intermediate. XRD refinement results: O3 phase 85 mol%, O2 phase 15 mol%.
[0055] S3: Take 100g of intermediate, 1.0g of lanthanum oxide, 1.0g of cerium oxide, and 1.1g of lithium carbonate, add ethanol, ball mill at 380r / min for 4.5h, and dry to obtain doped mixed powder.
[0056] S4: The doped powder was placed in a tube furnace and heated to 570°C at a rate of 2°C / min under an oxygen atmosphere (oxygen flow rate 4L / min), held at that temperature for 5.5 hours, and then cooled with the furnace. The powder was then pulverized and passed through a 250-mesh sieve to obtain the target material LiCo. 0.979 Al 0.021 O2@LiCo 0.952 La 0.048 O2.
[0057] Product characteristics: Shell thickness 2nm (TEM); O3:O2 = 17:3 ≈ 5.67:1; The compacted density is 4.23 g / cm³.
[0058] Battery performance: The retention rate after 50 cycles at 4.7V / 1C is 85%.
[0059] Example 6 This embodiment discloses a method for preparing an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material, including the following steps: S1: Weigh 100g cobalt carbonate, 20.86g lithium hydroxide, and 1.6g zirconium nitrate to make Li:(Co+Zr)=1.03:1 and Co:Zr=177:1; add 200mL of deionized water to prepare a slurry with a solid content of 42wt%, and spray dry (inlet temperature 210℃, outlet temperature 90℃) to obtain precursor powder.
[0060] S2: The precursor powder was placed in a tube furnace and heated to 910℃ at a rate of 3.5℃ / min under an oxygen atmosphere (oxygen flow rate 8L / min). It was then sintered at this temperature for 9.5h and cooled with the furnace to obtain a heterogeneous intermediate. XRD refinement results: O3 phase 85mol%, O2 phase 15mol%.
[0061] S3: Take 100g of intermediate, 1.2g of yttrium oxide, 1.0g of strontium oxide, and 0.9g of lithium carbonate, add ethanol, ball mill at 420r / min for 4h, and dry to obtain doped mixed powder.
[0062] S4: The doped powder was placed in a tube furnace and heated to 610℃ at a rate of 2.5℃ / min under an oxygen atmosphere (oxygen flow rate 6L / min), held at that temperature for 4.5h, and then cooled with the furnace; it was then pulverized and passed through a 250-mesh sieve to obtain the target material LiCo. 0.982 Al 0.018 O2@LiCo 0.948 La 0.052 O2.
[0063] Product characteristics: Shell thickness 2.5 nm (TEM); O3:O2 = 17:3 ≈ 5.67:1; The compacted density is 4.26 g / cm³.
[0064] Battery performance: The retention rate after 50 cycles at 4.7V / 1C is 88%.
[0065] Example 7 This embodiment discloses a method for preparing an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material, including the following steps: S1: Weigh 100g of cobalt tetroxide, 47.59g of lithium carbonate, and 1.2g of aluminum nitrate to make Li:(Co+Al)=1.03:1 and Co:Al=221:1; add 200mL of deionized water to prepare a slurry with a solid content of 42wt%, and spray dry (inlet temperature 210℃, outlet temperature 90℃) to obtain precursor powder.
[0066] S2: The precursor powder was placed in a tube furnace and heated to 870℃ at a rate of 2℃ / min under an oxygen atmosphere (oxygen flow rate 5L / min). It was then sintered at this temperature for 12 hours and cooled in the furnace to obtain a heterogeneous intermediate. XRD refinement results: O3 phase 80mol%, O2 phase 20mol%.
[0067] S3: Take 100g of intermediate, 1.2g of nano-lanthanum oxide, and 0.6g of lithium carbonate, add ethanol, ball mill at 300r / min for 5h, and dry to obtain doped mixed powder.
[0068] S4: The doped powder was placed in a tube furnace and heated to 530°C at a rate of 1.5°C / min under an oxygen atmosphere (oxygen flow rate 5 L / min), held at that temperature for 6 hours, and then cooled with the furnace. The powder was then pulverized and passed through a 250-mesh sieve to obtain the target material LiCo. 0.988 Al 0.012 O2@LiCo0.972 La 0.028 O2.
[0069] Product characteristics: Shell thickness 0.5 nm (TEM); O3:O2 = 4:1; The compacted density is 4.21 g / cm³.
[0070] Battery performance: The retention rate after 50 cycles at 4.7V / 1C is 83%.
[0071] Comparative Example 1 This comparative example discloses a method for preparing a lithium cobalt oxide cathode material, including the following steps: Cobalt tetroxide and lithium carbonate were mixed evenly according to the molar ratio of Co in cobalt tetroxide to Li in lithium carbonate being 1:1.07. Sintering: The mixture was calcined in air at 900°C for 10 hours to obtain lithium cobalt oxide cathode material.
[0072] Comparative Example 2 The only difference between this comparative example and Example 1 is that step S4 is omitted; otherwise, they are exactly the same as Example 1.
[0073] X-ray diffraction (XRD) analysis was performed on the modified lithium cobalt oxide cathode materials prepared in the examples and comparative examples. Specific test conditions were as follows: The instrument used was a Dandong Haoyuan XRD instrument, model DX-2700BH. The radiation source was Cu Kα, the tube voltage was set to 40 kV, and the tube current was set to 30 mA. During the scanning process, the scanning rate was controlled at 2° / min to ensure data accuracy. The 2θ angle scanning range was 10° to 80° to cover a wider range of material structure information.
[0074] Lithium-ion battery cycle performance testing: The lithium cobalt oxide cathode materials prepared in each example and comparative example were made into cathode sheets and assembled into lithium-ion batteries. Cycle performance testing was then conducted under 1C and 4.7V cutoff voltage conditions. The specific steps were as follows: Lithium cobalt oxide cathode material, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) were prepared in a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) was added and mixed, then stirred on a magnetic stirrer until homogeneous. The prepared slurry was coated onto an electrode sheet and transferred to a vacuum drying oven for vacuum drying at 120℃ for 12 hours. The dried electrode sheet was cut into 10mm round pieces to obtain the cathode sheet for battery assembly. In a glove box, the cathode shell, cathode sheet, separator, lithium sheet, and negative shell were assembled in that order, using LiPF6 electrolyte. The assembled product was a lithium-ion battery. The present invention uses the LANHECT2001A charge-discharge instrument of Wuhan Lanbo Electronics Co., Ltd. to conduct cycle performance tests on the obtained battery.
[0075] Figure 1 The XRD patterns of the cathode materials obtained in Example 1 and Comparative Example 1 are shown. No obvious impurity phase diffraction peaks were observed in the XRD patterns of either material, indicating high product phase purity. The (003) diffraction peak of the modified lithium cobalt oxide obtained in Example 1 shifts to a lower angle compared to Comparative Example 1, while the (104) diffraction peak shows the same trend, indicating a change in the lattice parameters of the modified material. Rietveld refinement results show that the O3 phase in the sample of Example 1 is 85 mol%, and the O2 phase is 15 mol%, confirming that the modified material is an O3 / O2 heterogeneous composite structure.
[0076] Figure 4 , Figure 5 The images show SEM images of the cathode materials obtained in Example 1 and Comparative Example 1, respectively. The comparison shows that the material obtained in Example 1, after undergoing in-situ construction of an O3 / O2 heterogeneous structure in step S1, bulk M doping in step S1, and surface X shell modification in steps S3-S4, exhibits a more regular secondary particle morphology and a denser surface. This is beneficial for improving the structural stability and interface protection capability of the particles under 4.7V high-voltage deep lithium delithiation conditions, forming the microstructural basis for its long-cycle, low-attenuation performance.
[0077] Figure 6 The discharge specific capacity cycling curves of the cathode materials obtained in Example 1 and Comparative Example 1 at 25°C, 4.7V cutoff voltage, and 1C rate are shown. The capacity retention rate of the material in Example 1 after 50 cycles is 90%, which is significantly higher than that of Comparative Example 1 (46%), indicating that the modified system of the present invention can effectively slow down the capacity decay under ultra-high voltage of 4.7V.
[0078] The cycle performance of each lithium cobalt oxide coin cell was tested at 4.7V and 1C rate at 25℃, and the capacity retention rate after 50 cycles was calculated. The test results are shown in Table 1. Table 1 Performance comparison of each embodiment and comparative example
[0079] From Table 1, we can obtain: The positive electrode materials prepared using Examples 1 to 7 of the present invention all exhibit superior cycle stability, and after 50 cycles, the capacity retention rate can be maintained within a favorable range of 79% to 90%.
[0080] As shown in Table 1, the seven sets of embodiments with different modification ratios and process parameters of the present invention exhibit superior compaction density and cycle retention rate under ultra-high voltage conditions of 4.7V compared to traditional pure O3 lithium cobalt oxide and O3 / O2 composite lithium cobalt oxide prepared by the lithium-sodium ion exchange method in Comparative Example 2. Among them, Examples 1, 3, and 6, which are multi-component composite doped with optimal sintering parameters, show the best performance, while Example 7 maintains an 83% retention rate even at a relatively low doping level.
Claims
1. A method for preparing an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material, characterized in that: Includes the following steps: S1: Weigh out the cobalt source, lithium source and dopant element M in nitrate or acetate according to the molar ratio Li:(Co+M)=1.02~1.05:1 and Co:M=50~250:1, then add deionized water to prepare a slurry, and spray dry the slurry to obtain the precursor powder. S2: The precursor powder is placed in a tube furnace and heated to 850-950°C at a heating rate of 2-5°C / min under an oxygen atmosphere. It is then sintered at a constant temperature for 8-12 hours and cooled with the furnace to obtain a heterogeneous intermediate with an O3 / O2 heterogeneous structure. S3: Mix the heterogeneous intermediate, the nano-oxide doped with element X, and lithium carbonate, with the nano-oxide comprising 1 to 3 parts and the lithium carbonate comprising 0.5 to 1.5 parts per 100 parts by mass of the heterogeneous intermediate. Add ethanol as a dispersion medium and ball mill for 3-5 hours. After drying, a doped mixed powder is obtained. S4: Place the doped mixed powder in a tube furnace, heat it to 500-650°C at a heating rate of 1-3°C / min under an oxygen atmosphere, hold it at that temperature for 4-6 hours, and then cool it with the furnace; pulverize the calcined product and pass it through a 300-mesh sieve to obtain an O3 / O2 heterogeneous composite lithium cobalt oxide cathode material with doped element X on the surface.
2. The preparation method of the O3 / O2 heterogeneous composite lithium cobalt oxide cathode material according to claim 1, characterized in that: In step S1, the cobalt source is at least one of cobalt tetroxide and cobalt carbonate.
3. The method for preparing the O3 / O2 heterogeneous composite lithium cobalt oxide cathode material according to claim 1, characterized in that: In step S1, the lithium source is at least one of lithium carbonate and lithium hydroxide.
4. The method for preparing the O3 / O2 heterogeneous composite lithium cobalt oxide cathode material according to claim 1, characterized in that: In step S1, the doping element M is at least one of Al, Mg, Zr, and Ti.
5. The method for preparing the O3 / O2 heterogeneous composite lithium cobalt oxide cathode material according to claim 1, characterized in that: In step S3, the doping element X is at least one of La, Ce, Y, and Sr.
6. The method for preparing the O3 / O2 heterogeneous composite lithium cobalt oxide cathode material according to claim 1, characterized in that: In step S2, the oxygen flow rate is 5~10L / min.
7. The method for preparing the O3 / O2 heterogeneous composite lithium cobalt oxide cathode material according to claim 1, characterized in that: In step S4, the oxygen flow rate is 2~8 L / min.
8. An O3 / O2 heterogeneous composite lithium cobalt oxide cathode material, characterized in that: The cathode material obtained by the preparation method according to any one of claims 1-7 comprises a core crystal structure and a doped protective shell covering the core crystal structure; the core crystal structure has LiCo 1-x M x The composition of O2, wherein the doped protective shell has LiCo 1-y X y The composition of O2, wherein 0.01≤x≤0.05, 0.02≤y≤0.08; the chemical composition of the cathode material is represented as LiCo. 1-x M x O2@LiCo 1-y X y O2.
9. A positive electrode sheet, comprising a positive electrode active material layer, characterized in that, The positive electrode active material layer comprises the O3 / O2 heterogeneous composite lithium cobalt oxide positive electrode material as described in claim 8.
10. A lithium-ion battery, comprising a positive electrode, characterized in that, The positive electrode is the positive electrode as described in claim 9.
